Compliance with the World Health Organization's 2016 prenatal care contact recommendation reduces the incidence rate of adverse birth outcomes among pregnant women in northern Ghana. - Leticia Achangebe Akum; Eunice Amina Offei; Mary Rachael Kpordoxah; Daudi Yeboah; Abdul-Nasir Issah; Michael Boah (PLoS ONE, 2023)
Background Children born with adverse birth outcomes (ABOs) have a greater risk of mortality, stunting, and poor cognitive development. In 2016, the World Health Organization (WHO) recommended at least eight antenatal care (ANC) contacts before delivery for a healthy mother and baby. We examined the association between compliance with this recommendation and the risk of ABOs, such as low birthweight (LBW) and preterm birth (PTB), in the Tamale Metropolitan Area of the northern region of Ghana. Methods We conducted a cross-sectional study in the Tamale Metropolis of the northern region of Ghana. We analysed a systematic random sample of 402 postnatal women aged 15-49 drawn from five public health facilities. We gathered information electronically on their birth outcomes, specifically their birthweight and gestation at delivery, using a structured questionnaire. Information on women's background characteristics, including the number of ANC contacts made before delivery, was also collected. The association between the number of ANC contacts and ABOs was investigated using regression models. Results We found that 37.6% (95% CI: 32.9, 42.4) of our sample had at least eight ANC contacts before delivery. We estimated that 18.9% of babies were born prematurely and 9.0% were born LBW. ABOs were found in 22.9% (95% CI: 19.0, 27.3) of babies. A minimum of eight ANC contacts before delivery reduced the risk of ABOs (adjusted IRR = 0.43; 95% CI: 0.25, 0.73), PTB (AOR = 0.28; 95% CI: 0.14, 0.58), and LBW (AOR = 0.36; 95% CI: 0.14, 0.91). Conclusion In the current study's setting, about a quarter of newborns have ABOs, jeopardising their survival, health, and development. Compliance with at least eight ANC contacts prior to birth was associated with a reduced incidence rate ratio of ABOs. However, less than four out of every ten pregnant women make at least eight ANC contacts before delivery. Efforts are needed to increase coverage of eight contacts among pregnant women before delivery to reduce the risk of ABOs in the study setting.